Editorial : The Thirtieth Anniversary of Our MA In Applied Linguistics To ELT: A Commitment to the Critical Dimension of Language Education - Bonilla Medina, Ximena; Quintero Polo, Álvaro Hernán (Colombian Applied Linguistics Journal, 2021)
This issue of the Colombian Applied Linguistics Journal, CALJ, coincides with the commemoration of the thirtieth anniversary of the MA in Applied Linguistics to ELT of Universidad Distrital Francisco José de Caldas. Every actor of the MA embraces an evolving critical approach to researching the humanistic, social, cultural, and political dimensions of language education. To be consistent with an intended critical perspective in the face of language issues that relate to the practices of social agents within and outside educational settings, every actor of the MA does not want to be only a mere spectator of what is happening in Colombia and around the world. The Colombian Applied Linguistics Journal is itself an illustration of the activities originated in the MA program that account for such evolution.